The Taste-Masking Mechanism of Chitosan at the Molecular Level on Bitter Drugs of Alkaloids and Flavonoid Glycosides from Traditional Chinese Medicine - Yaqi Xu; Qianwen Sun; Wei Chen; Yanqi Han; Yue Gao; Jun Ye; Hongliang Wang; Lili Gao; Yuling Liu; Yanfang Yang (Molecules, 2022)
Taste masking of traditional Chinese medicines (TCMs) containing multiple bitter components remains an important challenge. In this study, berberine (BER) in alkaloids and phillyrin (PHI) in flavonoid glycosides, which are common bitter components in traditional Chinese medicines, were selected as model drugs. Chitosan (CS) was used to mask their unfriendly taste. Firstly, from the molecular level, we explained the taste-masking mechanism of CS on those two bitter components in detail. Based on those taste-masking mechanisms, the bitter taste of a mixture of BER and PHI was easily masked by CS in this work. The physicochemical characterization results showed the taste-masking compounds formed by CS with BER (named as BER/CS) and PHI (named as PHI/CS) were uneven in appearance. The drug binding efficiency of BER/CS and PHI/CS was 50.15 ± 2.63% and 67.10 ± 2.52%, respectively. The results of DSC, XRD, FTIR and molecular simulation further indicated that CS mainly masks the bitter taste by disturbing the binding site of bitter drugs and bitter receptors in the oral cavity via forming hydrogen bonds between its hydroxyl or amine groups and the nucleophilic groups of BER and PHI. The taste-masking evaluation results by the electronic tongue test confirmed the excellent taste-masking effects on alkaloids, flavonoid glycosides or a mixture of the two kinds of bitter components. The in vitro release as well as in vivo pharmacokinetic results suggested that the taste-masked compounds in this work could achieve rapid drug release in the gastric acid environment and did not influence the in vivo pharmacokinetic results of the drug. The taste-masking method in this work may have potential for the taste masking of traditional Chinese medicine compounds containing multiple bitter components.